solve this question anyone
Attachments:
![](https://hi-static.z-dn.net/files/dda/9f2dfe3016900a5fdae964acd37d6ae3.jpg)
Answers
Answered by
3
Given :
(a-b) = 7 and ab = 18
To find out :
i ) a+b
- Solution :-
Using :- (a-b)² = a² + b² - 2ab
=> (7)² = a² + b² - 2(18)
=> 49 = a² + b² - 36
=> a² + b² = 49 + 36
=> a² + b² = 85 ________[equation -1]
Now substituting [equation -1] in:-
=> (a+b)² = a² + b² + 2ab
=> (a+b)² = 85 + 2(18)
=> (a+b)² = 85 + 36
=> (a+b)² = 121
=> a+b = 11
_______________________________________
ii ) a² - b²
- Solution :-
Using :- a² - b² = (a+ b)(a-b)
=> a² - b² = ( 11 )( 7 )
=> a² - b² = 77
i ) a + b = 11
ii ) a² - b² = 77
Similar questions